2021
DOI: 10.1136/archdischild-2020-320761
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate during the first 24 hours in term-born infants

Abstract: ObjectiveHeart rate (HR) is an important clinical parameter in newborn infants, but normal ranges are poorly defined. Our aim was to establish normal reference ranges and individual variations in HR as obtained by auscultation in healthy term-born infants during the first 24 hours of life.DesignObservational study.SettingSingle hospital in Norway.MethodsHR was assessed by auscultation for 30 s at 2, 4, 8, 16 and 24 hours of age. Auscultation was validated against ECG recordings.SubjectsHealthy term-born infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Other factors that have been reported to influence initial neonatal HR include sleep–wake state, sex, and body temperature [ 19 ]. In addition, the timing of cord clamping has been reported to have an effect on initial neonatal HR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors that have been reported to influence initial neonatal HR include sleep–wake state, sex, and body temperature [ 19 ]. In addition, the timing of cord clamping has been reported to have an effect on initial neonatal HR.…”
Section: Discussionmentioning
confidence: 99%
“…Studies describing HR changes just after birth have demonstrated a peak HR reached within one minute [ 17 , 18 ]. Factors such as mode of delivery, sleep–wake patterns, skin-to-skin care, gender, and body temperature have been shown to influence initial neonatal HR [ 19 ]. It has been further shown that the HR of neonates born vaginally is significantly higher up to one hour after birth than those born by Cesarean section [ 20 ].…”
Section: Introductionmentioning
confidence: 99%